Ethnoreligious Otherings and Passionate Conflicts - Magcamit, Michael (Oxford University Press, 2022)
Departing from the mainstream practice and conventional wisdom of materialist and rationalist accounts of internal and intrastate conflicts, the book demonstrates how and why emotions, symbolic predispositions, and perceptions are just as powerful and useful in understanding and explaining these phenomena. By uncovering the invisible albeit concrete emotive, symbolic, and perceptual causal mechanisms underpinning ethnoreligious otherings and the resulting violent protracted conflicts, the book aims to help address the incongruence between how the actual actors operating within these contexts think and act and the existing theories and models of how they are expected to behave. Accordingly, the book has three main goals. First, to highlight the centrality of emotions, symbolic predispositions, and perceptions in providing a more holistic and realistic understanding of otherings and conflicts. Second, to illustrate how the ethnoreligious othering framework developed and applied in the study bolsters and advances process tracing explanations by systematically incorporating context-specific intersubjective meanings into causal accounts of the events under investigation. And third, to emphasize the importance of recognizing religion and nationalism as legitimate constituents and instruments of contemporary realpolitik by underlining their enduring security utility and essence at individual, group, and state levels. As argued and established throughout the book, because the causal mechanisms driving ethnoreligious otherings and passionate conflicts are simultaneously emitting and are propelled by deeply entrenched emotions, symbolic predispositions, and perceptions, achieving durable peace settlement requires reconciliation initiatives and regulation strategies that directly and unapologetically incorporate and address these neglected "immaterial" and "irrational" forces.